Imbalances in socio-economic development of regions of Russian Federation: problems and solutions - M. Yu. Makovetsky; D. V. Rudakov; K. A. Voropaev (Омский научный вестник: Серия "Общество. История. Современность")
The article examines factors and conditions of functioning of Federal districts in the Russian Federation, created to optimize the country’s governance as instruments of Federal state regulation of territorial development. The main attention is paid to the features and results of the Siberian Federal district, while they are analyzed in the context of modern socio-economic processes taking place in the Russian Federation. The strengths and weaknesses are identified, the most acute problems are revealed, which predetermined more than a modest dynamics of the main economic indicators in the development and caused a significant imbalance in their values in certain regions that are part of the Siberian Federal district. Possible ways of neutralizing negative trends in order to ensure positive changes in socioeconomic indicators, improve the quality of life, increase competitiveness and reduce the migration outflow of residents from Siberia to other regions of the Russian Federation are proposed